2019
DOI: 10.1002/ange.201906501
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Light‐Triggered Antimicrobial Indium Phosphide Quantum Dots

Abstract: The emergence of multidrug-resistant (MDR) pathogens represents one of the most urgent global public health crises.L ight-activated quantum dots (QDs) are alternative antimicrobials,w ith efficient transport, low cost, and therapeutic efficacy,and they can act as antibiotic potentiators, with am echanism of action orthogonal to small-molecule drugs.Furthermore,light-activation enhances control over the spatiotemporal release and dose of the therapeutic superoxide radicals from QDs.H owever,t he limited deep-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…There-fore, InP-based QDs emerged as an attractive alternative to CdSe QDs because they possess similar optoelectronic properties but a lower intrinsic toxicity, 3−5 which makes them suitable for applications spanning from optoelectronics to nanomedicine. 6,7 However, while the roles played by chemical composition, size and shape, 8 outer inorganic and organic shells 9 have been intensively investigated in toxicity studies, 10 other mechanisms need to be thoroughly dissected for a safe use of QDs in biomedicine. 11 These include the route of uptake and the intracellular trafficking events up to secretion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There-fore, InP-based QDs emerged as an attractive alternative to CdSe QDs because they possess similar optoelectronic properties but a lower intrinsic toxicity, 3−5 which makes them suitable for applications spanning from optoelectronics to nanomedicine. 6,7 However, while the roles played by chemical composition, size and shape, 8 outer inorganic and organic shells 9 have been intensively investigated in toxicity studies, 10 other mechanisms need to be thoroughly dissected for a safe use of QDs in biomedicine. 11 These include the route of uptake and the intracellular trafficking events up to secretion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HeLa cells are commonly used as the model cell lines for toxicity assessment in vitro, and they were also adopted in this study. 52,53 After incubation with CWS NCs for 24 h, the viability of HeLa cells was approximately 100%, even at the concentration of CWS NCs up to 64 μg mL −1 (Figure 5a). SEM and elemental mapping images (Figure S19) show that few CWS NCs attach to the surface of HeLa cells, though HeLa cells were exposed to 100 μg mL −1 of CWS NCs.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 It has been experimentally demonstrated that InP core/shell or InP core/alloy shell systems exhibit high ON times when probed in single-particle level. 24,25 Hydrophilic InP quantum dots (QDs) are used as targeted bioimaging agents in detection of early stage cancer, 26 as a therapeutic agent for the selective elimination of multidrug resistant bacteria in human cells, 27 and for immunoassays. 28 In a recent report, Dennis and co-workers have extended the emission characteristics of InP to the first optical tissue window (650−950 nm) using an inverted QD heterostructure (ZnSe/ InP/ZnS) and demonstrated its specific application for multiplexed fluorescence imaging.…”
Section: ■ Introductionmentioning
confidence: 99%